Venous Configurations of the Anterior Cubital Region - Gościcka, Danuta; Flisiński, Piotr (Anthropological Review, 1992)
Venous configurations of the anterior cubital region were examined on the sample of 203 country children. The occurence of vessel connections of Y -type was found in 91,9%. The variant had 10 modificatins (a-j). Modification of j-type which was observed in boys was the most ramified one. The relation between the kind of the work and the kind of the vessel configuration has been suggested.